The global emergence of a novel Streptococcus suis clade associated with human infections - Xingxing Dong; Yanjie Chao; Yang Zhou; Rui Zhou; Wei Zhang; Vincent A. Fischetti; Xiaohong Wang; Ye Feng; Jinquan Li (EMBO Molecular Medicine)
Abstract Streptococcus suis, a ubiquitous bacterial colonizer in pigs, has recently extended host range to humans, leading to a global surge of deadly human infections and three large outbreaks since 1998. To better understand the mechanisms for the emergence of cross‐species transmission and virulence in human, we have sequenced 366 S. suis human and pig isolates from 2005 to 2016 and performed a large‐scale phylogenomic analysis on 1,634 isolates from 14 countries over 36 years. We show the formation of a novel human‐associated clade (HAC) diversified from swine S. suis isolates. Phylogeographic analysis identified Europe as the origin of HAC, coinciding with the exportation of European swine breeds between 1960s and 1970s. HAC is composed of three sub‐lineages and contains several healthy‐pig isolates that display high virulence in experimental infections, suggesting healthy‐pig carriers as a potential source for human infection. New HAC‐specific genes are identified as promising markers for pathogen detection and surveillance. Our discovery of a human‐associated S. suis clade provides insights into the evolution of this emerging human pathogen and extend our understanding of S. suis epidemics worldwide.